War, Revolt and Sacred Space : Cambrai and the Southern Netherlands, 1566-c.1621 - Spicer, Andrew (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
Churches and sacred spaces were devastated by warfare and confessional violence in the southern Netherlands during the late sixteenth century. This monograph explores how these churches were rebuilt, the material culture of worship repaired or replaced, and their sanctity restored. Work began in the immediate aftermath of the iconoclasm and rebellion of 1566-67 and continued into the early seventeenth century. How this was achieved and the multiple agents involved is analysed across the Francophone dioceses of the ecclesiastical province of Cambrai. This restoration coincided with the reassertion and revitalisation of Catholic devotion embodied in the Tridentine decrees. Drawing on extensive archival research, as well as buildings, church furnishings and religious art, this monograph provides an alternative perspective on political upheaval and Catholic renewal in the southern Netherlands under Philip II of Spain and the Archdukes Albert and Isabella.